Thermal Properties, Crystallinity, and Oxygen Permeability of Na-montmorillonite Reinforced Plasticized Poly(lactic acid) Film - Yuniarto, Kurniawan; Purwanto, Yohanes Aris; Purwanto, Setyo; Welt, Bruce A.; Purwadaria, Hadi Karia; Sunarti, Titi Candra (Makara Journal of Technology, 2016)
Introducing unmodified organically clay/Na-montmorillonite (Na-MMT) was applied into plasticized poly(lactic acid) PLA to produce film composites by direct casting. Film composite structure, the crystallinity degree and form, and thermal properties were carried out using X-ray diffraction and differential scanning calorimetry. The effect of Na- MMT to the tortuous path and the crystallinity degree in the plasticized film composites were calculated in oxygen barrier properties. Chromatogram film composites resulted in an intercalated structure that showed peak diffraction angle shift at about 0.2o. Then, a peak diffraction pattern was indicated in α-form crystal structure. Plasticized PLA has a crystallinity degree at 34%, and the addition of Na-MMT increased to 52%. Glass transition temperature improved from 53 °C to 57 °C, and melting temperature remained stable at 167 °C. Filling Na-MMT into plasticized PLA caused to enhance a tortuous path about 28% and improved the oxygen permeability to 80%. As a result, the addition of Na- MMT of 3% into plasticized PLA during film composite preparation using the mixing method resulted in balancing properties related to the crystallinity degree, thermal properties, and oxygen barrier properties.